FAKTOR-FAKTOR INTERNAL DAN EKSTERNAL YANG BERHUBUNGAN DENGAN PEMILIHAN PASAR PETANI MANGGA - Elly Rasmikayati; Aurelia Fadhilah Sari; Rani Andriani Budi Kusumo; Bobby Rachmat Saefudin; Nur Syamsiyah (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2020)
The selection of the market that partners with farmers is based on the ability of farmers to attract the attention of buyers. But in reality, most mango farmers have a high dependency to sell their harvest to middlemen. This study aims to analyze internal and external factors related to market selection for mango farmers. This research is a quantitative study conducted in Sedong District, Cirebon Regency, West Java. The research method uses the survey method. The research sample was taken using a simple random sampling technique such that a sample size of 50 people was obtained. The data analysis tool used is crosstabulation analysis. The results showed that internal factors that have a directly proportional relationship to market selection are the level of education, number of trees, ownership of transportation, and activeness in farmer groups, while internal factors that have an inverse relationship with market selection are age and farming experience. The eexternal factors that have a directly proportional relationship to market selection are distance to market, travel time to market, and government contribution. While internal factors such as level of trust, access to information, and activeness in participating in counseling, and external factors such as conducting counseling have no relationship with market selection.